Bioaugmentation improves the anaerobic co-digestion of cadmium-containing plant residues and cow manure. (15th November 2021) - Guo, Qian; Ji, Jing; Ling, Zhenmin; Zhang, Kai; Xu, Rong; Leng, Xiaoyun; Mao, Chunlan; Zhou, Tuoyu; Wang, Haoyang; Liu, Pu; Li, Xiangkai
Abstract: Phytoremediation causes a large quantity of phytoremediation residues rich in heavy metals (HMs). This kind of plant residue can be used as a substrate for anaerobic digestion (AD) to reduce the content of HM-containing biomass, but high concentrations of HMs will inhibit the digestion efficiency and reduce the conversion efficiency of plant residues. Bioaugmentation may be an effective method to improve the degradation efficiency and methane yield of plant residues rich in HMs. In this study, a cellulose-degrading anaerobic bacteria Paracoccus sp. Termed strain LZ-G1 was isolated from cow dung, which can degrade cellulose and simultaneously adsorb Cd 2+ . The Cd 2+ (10 mg/L)-adsorbtion efficiency and cellulose (463.12 g/kg)-degradation rate were 65.1 % and 60.59 %, respectively. In addition, using the strain LZ-G1 bioaugmented Cd 2+ -containing plant residues and cow manure mixed AD system, the system's biogas and methane production significantly increased (98.97 % and 142.03 %, respectively). During the AD process, the strain LZ-G1 was successfully colonized in the digestion system. Furthermore, the microbial community analysis revealed that LZ-G1 bioaugmentation alleviates the toxicity of free Cd 2+ to the microbial community in the AD system, regulates and restores the archaea genus dominant in the methanogenesis stage, and restores the relative abundance of dominant bacteria associated with biomass hydrolysis. The restoration of the microbial community increased the biogas yield and methane production rate. Thus, bioaugmentation provides an easy and a feasible method for the actual on-site treatment of HM-rich phytoremediation residues. Graphical abstract: Image 1 Highlights: Paracoccus sp. LZ-G1 can degrade cellulose and adsorb cadmium. The strain LZ-G1 can improve the methane yield of cadmium-containing plants. The strain LZ-G1 protects microbial communities from cadmium inhibition. LZ-G1 bioaugmentation promotes AD of phytoremediation plant residues.